Inulin Exerts Beneficial Effects on Non-Alcoholic Fatty Liver Disease via Modulating gut Microbiome and Suppressing the Lipopolysaccharide-Toll-Like Receptor 4-Mψ-Nuclear Factor-κB-Nod-Like Receptor Protein 3 Pathway via gut-Liver Axis in Mice - Bao, Ting; He, Fang; Zhang, Xiaoxia; Zhu, Lili; Wang, Zhen; Lu, Haixia; Wang, Ting; Li, Yiwei; Yang, Shaoqi; Wang, Hao (Frontiers in Pharmacology, 2020)
Background: Non-alcoholic fatty liver disease (NAFLD) is a common metabolic disease worldwide with chronic low-grade inflammation and alteration of gut microbiota. Inulin (INU) has been confirmed to exhibit benefit for metabolic diseases. The aim of this study was to clarify the effects and mechanism of INU on NAFLD inflammation via gut-liver axis. Methods: C57BL/6 mice were randomly divided into four groups: normal diet group (ND); high-fat diet group (HFD); ND with INU group (ND-INU); HFD with INU group (HFD-INU). After 14 weeks of feeding, mice were sacrificed and associated indications were investigated. Results: Significant increases of body weight, liver weight, liver biochemical aspartate aminotransferase, alanine aminotransferase, triglyceride, total cholesterol and pro-inflammatory indicators (Lipopolysaccharide, interleukin (IL)-18, IL-1β, TNF-α and IL-6), as well as a reduction of plasma IL-10 were observed in HFD group, while INU treatment restored these abnormal indicators. The ratio of hepatic macrophages (Mψs) and Toll-like receptor 4+ Mψs were both reduced with INU intervention. Nuclear factor-κB, nod-like receptor protein 3, apoptosis-associated speck-like protein and caspase-1 were decreased in HFD-INU group. Additionally, the results of 16S rRNA sequencing and analysis showed that INU administration modulated the composition of gut microbial community in NAFLD mice by up-regulating the abundances of Akkermansia and Bifidobacterium as well as down-regulating the abundances of Blautia and the ratio of Firmicutes/Bacteroidetes. Short-chain fatty acids including acetic acid, propionic acid and butyric acid, were increased with INU treatment. Correlation analysis revealed close relationships among inflammatory indicators, metabolic indicators as well as gut microbiota/its metabolite short-chain fatty acids. Conclusion: INU prevents NAFLD via modulating gut microbiota and suppressing Lipopolysaccharide-Toll-like receptor 4-Mψ-Nuclear factor-κB-nod-like receptor protein 3 inflammatory pathway via the gut-liver axis.